1992
DOI: 10.1111/j.1475-4991.1992.tb00397.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERNATIONAL COMPARISONS OF EARNINGS INEQUALITY FOR MEN IN THE 1980s

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Since then it has risen at a steady rate, reversing the long-term trend toward declining inequality. A similar upswing in inequality has been observed in some other industrial societies besides the United States, suggesting that the phenomenon has an international character (Green, Coder, and Ryscavage 1992;Freeman and Katz 1995;OECD 1995a;Ram 1997). 3 One question that arises from these stylized facts regarding the recent inequality experience of the advanced industrial societies is whether the great U-turn is, like arguably the Kuznets curve, an inherent tendency linked to late stages of industrial (or postindustrial) development.…”
Section: Income Inequality Trendsmentioning
confidence: 73%
“…Since then it has risen at a steady rate, reversing the long-term trend toward declining inequality. A similar upswing in inequality has been observed in some other industrial societies besides the United States, suggesting that the phenomenon has an international character (Green, Coder, and Ryscavage 1992;Freeman and Katz 1995;OECD 1995a;Ram 1997). 3 One question that arises from these stylized facts regarding the recent inequality experience of the advanced industrial societies is whether the great U-turn is, like arguably the Kuznets curve, an inherent tendency linked to late stages of industrial (or postindustrial) development.…”
Section: Income Inequality Trendsmentioning
confidence: 73%
“…have found that income inequality in the U.S. has not only been growing, but growing at an increasing rate (Chevan and Stokes 2000;Gottschalk 1994, 1995;Green et al 1992;Freeman 1997;Freeman and Katz 1995;Levy and Murnane 1992;Massey 1996;Sassen 1990). Further, not only has income inequality been increasing for the nation as a whole, but inequality has been increasing within each population subgroup (gender, race, age, residence, etc.…”
mentioning
confidence: 96%
“…14 This finding, of course, does not prove that these changes are produced by the same causal factor, nor does it indicate which of several possible mechanisms should be regarded as the most plausible factor. Still, the results indicate that more general 'global' factors, such as technological change, shifts in the industrial structure, intensified international competition, etc., might have played a significant role in the changing structure of the earnings distribution (see further Gottshalk & Joyce 1991;Green, Coder & Ryscavage, 1992).…”
Section: Methodsmentioning
confidence: 98%